Suppression of Ripples of Controllable Rectifiers for Power Supply of Magnetic Systems - M. S. Lur’e; O. M. Lur’e; A. S. Frolov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A number of requirements are imposed on installations associated with regulated DC sources, including low voltage and current ripple in the load, as well as a wide range of output current variation. Such installations are traditionally made on controlled rectifiers or pulse-width converters in which voltage ripples are always present. The paper considers a method for reducing the voltage ripple of powerful rectifiers for powering magnetic systems based on the insertion of a compensating voltage equal in magnitude and opposite in phase to the ripple voltage into the load circuit. The possibility of using ripple compensators connected in parallel and in series with the load, as well as methods of obtaining a compensating voltage is shown. Methods for obtaining compensating voltage are given. In order to exclude the magnetization of the ripple compensator transformer, it is proposed to use several versions of the compensating transformer and the inclusion of ripple compensators. Practical schemes of passive compensators (with a demagnetizing circuit and a bifilar winding) are analyzed. The problem of developing ripple compensators for multiphase rectifiers, as well as ways to solve it, is considered. Practical recommendations for choosing a core material and calculating a transformer are given. On the basis of the presented theoretical and practical considerations for the design of the ripple compensators, simulation models have been developed in the Simulink pack-age of the MATLAB program. A technique for studying ripple compensators using the simulation models of a symmetrical 12-pulse rectifier that has been developed is presented. The results of simulation of passive ripple compensators, performed in two versions, showed their effectiveness, while the scheme was relatively simple and economic costs were relatively low. Also, the time of setting the set current in the system in the presence of a ripple compensator increases by no more than 3 %, and the accuracy and stability of operation do not change.